2016
DOI: 10.1038/srep38104
|View full text |Cite
|
Sign up to set email alerts
|

A low balance between microparticles expressing tissue factor pathway inhibitor and tissue factor is associated with thrombosis in Behçet’s Syndrome

Abstract: Thrombosis is common in Behçet’s Syndrome (BS), and there is a need for better biomarkers for risk assessment. As microparticles expressing Tissue Factor (TF) can contribute to thrombosis in preclinical models, we investigated whether plasma microparticles expressing Tissue Factor (TF) are increased in BS. We compared blood plasma from 72 healthy controls with that from 88 BS patients (21 with a history of thrombosis (Th+) and 67 without (Th−). Using flow cytometry, we found that the total plasma MP numbers we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 56 publications
(59 reference statements)
2
16
0
Order By: Relevance
“…The expression of Tissue Factor (TF) by microparticles was experimentally shown to contribute to the development of thrombosis (157). Using flow cytometry, it has been demonstrated that the total number of plasma microparticles was elevated in BD patients compared to healthy controls, as were microparticles characterized by TF and Tissue Factor Pathway Inhibitor (TFPI) (157).…”
Section: Small Vessel Vasculitismentioning
confidence: 99%
“…The expression of Tissue Factor (TF) by microparticles was experimentally shown to contribute to the development of thrombosis (157). Using flow cytometry, it has been demonstrated that the total number of plasma microparticles was elevated in BD patients compared to healthy controls, as were microparticles characterized by TF and Tissue Factor Pathway Inhibitor (TFPI) (157).…”
Section: Small Vessel Vasculitismentioning
confidence: 99%
“…The TF pathway plays a significant role in several bleeding and clotting disorders. 9,10 Tissue factor pathway inhibitor (TFPI) is the primary inhibitor of TF-induced coagulation in vivo. And TFPI cannot only inhibit activated factor Xa directly, but also inhibit VIIa/TF activity.…”
Section: Tissue Factor and Tissue Factor Pathway Inhibitormentioning
confidence: 99%
“…Indeed, three main mechanisms have been described so far by which neutrophils can contribute to thrombo-inflammation in either inflammatory or neoplastic conditions: (1) by the release of neutrophil extracellular traps (NETs); (2) by the formation of neutrophil-derived microparticles; and (3) via the hyperactivation of inflammasome. Interestingly, in BS the contribution of microparticles and inflammasome has been already suggested (9, 10), while the role of NETs is still under investigation.…”
Section: Introductionmentioning
confidence: 99%